Effect of Sea-Level Change on Deep-Sea Sedimentary Records in the Northeastern South China Sea over the past 42 kyr - Bin Wang; Huaiyan Lei; Fanfan Huang; Yuan Kong; Fulong Pan; Weidong Cheng; Yong Chen; Limei Guo (Geofluids)
We integrated multiple geochemical analysis of a 13.75 m-long core 973-4 recovered from the northeastern South China Sea (SCS) to detect the response of deep-sea sediment archives to sea-level change spanning the last 42 kyr. The age-depth model based on AMS 14C dating, together with the sediment grain size, shows an occurrence of turbidity current at around 14 kyr, which was associated with submarine landslides caused by gas hydrate dissociation. A dominantly terrigenous sediment input was supplied from southwestern Taiwan rivers. By synthesizing environment-sensitive indexes, four distinct stages of paleoenvironmental evolutions were recognized throughout the studied interval. Well-oxygenated condition occurred during the stage I (42.4-31.8 kyr) with low sea-level stand below -80 m, accompanied by flat terrigenous input. The largest amounts of terrigenous sediment input occurred during the late phase of stage II (31.8-20.4 kyr) with the lowest sea-level stand below -120 m because of a short distance from paleo-Taiwan river estuaries to the core location. An occurrence of Ca-enriched turbidity current disturbed the original sediments during the stage III (20.4-13.9 kyr). The stepwise elevated sea-level stand resulted in an enclosed (semi-enclosed) system and contributed to a relatively low-oxygen environment in deep ocean during the stage IV (13.9 kyr—present). Temporal variations of TOC and CaCO3 display contrary pattern synchronously, indicating a decoupled relationship between organic carbon burial and carbonate productivity. Our results highlight that these sedimentary records as reflected in the paleoenvironmental changes in the northeastern SCS were mainly driven by sea-level fluctuations and later, since the mid-Holocene, the strengthening East Asian summer monsoon (EASM) overwhelmed the stable sea level in dominating the environmental changes.